Can we predict the coronary angiography result?. (2nd May 2022) - Santos, M; Santos, H; Paula, S; Almeida, I; Almeida, S; Tavares, J; Santos, L; Almeida, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: It is estimated that 5-15% of patients admitted with suspected acute myocardial infarction (AMI) have no significant lesions on coronary angiography (>50%), an entity called MINOCA. Objective: To identify predictors of non-significant coronary lesions in patients admitted with AMI Methods: Based on a multicenter retrospective study, data collected from admissions between 2013 and 2020. Patients (pts) without data on cardiovascular history or uncompleted clinical data were excluded. Pts were divided in 2 groups (G): GA – pts with significant coronary lesions; GB - pts with non-significant coronary lesions. Results: MINOCA occurred in 1561 (20.6%) out of 6029 pts with AMI. There were no differences between G regarding age (p=0.745). GB pts were more frequently females (35.9% vs 24.9%, p<0.001), had lower rates of smoking habits (21.9% vs 26.9%, p<0.001), arterial hypertension (70.7% vs 73.4%, p=0.036), diabetes (31.1% vs 36.7%, p<0.001), past history of MI (13.9% vs 23.5%, p<0.001) and past history of stroke (5.0% vs 7.5%, p=0.002). There were no differences between G regarding symptoms at admission (p=0.359). At admission, GB had lower mean heart rate (76±18 vs 78±19, p=0.037), lower systolic arterial pressure (141±25 vs 144±28, p<0.001), lower rates of KK>1 (10% vs 12.2%, p=0.037), higher rates of atrial fibrillation (AF) (8.8% vs 6.8%, p=0.026), higher rates of normal ST-T segment (50.9% vs 29.6%, p<0.001), and lower BNP levels (99±36.9 vs 157±64, p<0.001). During hospitalization, GB pts used less diuretics (18.1% vs 26.1%, p<0.001) and inotropes (0.5% vs 1.8%, p=0.007). GB had a lower prevalence of left ventricle dysfunction (<50%) (20.4% vs 29.3%, p<0.001), and less need of mechanical ventilation (0.1% vs 1.0%, p<0.001), non-invasive ventilation (0.1% vs 1.6%, p<0.001) and provisory pacing (0.1% vs 0.5%, p=0.011). Logistic regression confirmed that being a female (p<0.001, OR 2.7), a non-smoker (p=0.002, OR 1.4), a non-diabetic (p=0.001, OR 1.45), AF (p=0.001, OR 1.8), normal QRS (p<0.001, OR 1.9) and normal LV function (p=0.009. OR 1.5) were predictors of MINOCA. The G were similar regarding in-hospital MACE outcomes (in-hospital death, stroke or MI) (p=0.658) and 1 year outcomes, namely 1 year mortality (p=0.709) and readmission of cardiovascular causa (p=0.290). Conclusion: Several clinical factor may help us predicting which patients will have a coronary angiography without significant lesions. However, the absence of significant lesions is not predictive of better in-hospital and 1 year prognosis.